KARAKTERISTIK STRUKTUR GENERIK TEKS CERPEN KARYA SISWA KELAS XI SMA NEGERI 1 LUBUK SIKAPING - M. Hafrison, Dina Devitry, Nursaid, (Universitas Negeri Padang, 2017)
This research aims to describe the following two points. First, describe the characteristics of the generic structure of short story text of students of grade XI SMA Negeri 1 Lubuk Sikaping. Second, describe Error of spelling in short story text made by students of grade XI SMA Negeri 1 Lubuk Sikaping. The method used in this research is descriptive method. The data discussed is qualitative data. The data were language devices in the form of written words taken from the object of research. The Sources of data in this study is short story texts of students of class XI class of 2015 SMA Negeri 1 Lubuk Sikaping. The instrument of this research is the researcher herself. Data were analyzed by describing, analyzing, and discussing data based on theory. The results of research are as follows. First, the researcher found 6 characteristics of short story text structure, namely abstract, orientation, complication, evaluation, resolution, and code in the writing of grade XI students of SMA Negeri 1 Lubuk Sikaping. Second, there were 3 spelling mistakes found, namely the use of capital letters, the use of prepositions and affixes, and the use of punctuation pronouns, nouns, verbs, adjectives, and adverbs in the writing students grade XI SMA Negeri 1 Lubuk Sikaping. Based on the results of the research it can be concluded two things. First, in writing the short story texts students of grade XI SMA Negeri 1 Lubuk Sikaping has used four text structure short stories namely orientation, complication, evaluation, and resolution. It was found that from 21 short story text that have been analyzed, only 5 short story text that uses the abstract and only 5 short story text that also uses the coda. Secondly, it was also found that when viewed from the spelling mistakes in the short story text written by the students of class XI SMA Negeri 1 Lubuk Sikaping, the most dominant mistake were the use of capital letters and the use of punctuation.Â Keywords: karakteristik struktur generik, ejaan, teks cerpen